2007
DOI: 10.1111/j.1365-2265.2007.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of remission of hyperprolactinaemia after long‐term withdrawal of cabergoline therapy

Abstract: Persistent remission of hyperprolactinaemia without any evidence of tumour re-growth after 24-96 months of CAB withdrawal occurred in the majority of patients with NTH and microprolactinoma and in about half of those with macroprolactinoma. Nadir PRL levels and maximal tumour diameter at CAB withdrawal of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 56 publications
(127 reference statements)
5
94
2
7
Order By: Relevance
“…To sum up, male sex does not exert crucial effect on surgical outcomes of prolactinomas. However, male gender was found to be closely associated with recurrence of hyperprolactinemia after DA withdrawal by Colao et al (5). In the present study, the preoperative PRL level and tumor invasion were found to be associated with early poor surgical outcomes by multivariate analysis, in line with most of the previous literature (16,17,22).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To sum up, male sex does not exert crucial effect on surgical outcomes of prolactinomas. However, male gender was found to be closely associated with recurrence of hyperprolactinemia after DA withdrawal by Colao et al (5). In the present study, the preoperative PRL level and tumor invasion were found to be associated with early poor surgical outcomes by multivariate analysis, in line with most of the previous literature (16,17,22).…”
Section: Discussionsupporting
confidence: 90%
“…Of these patients, 60.4% achieved normalization of PRL concentration, which was slightly lower than the previous report of a mixed series (16). At the latest follow-up, the total remission rate of our series might be superior to that of withdrawal of medication therapy (5,6).…”
Section: Discussioncontrasting
confidence: 70%
“…Згідно з дослідженнями, проведеними А. Соlа і співавт., лікування САВ протягом 24 місяців з вико-ристанням середньої терапевтичної дози препара-ту 1,5 мг у хворих з макроПРОЛ і 1 мг з мікроПРОЛ щотижня призводило до нормалізації рівня ПРЛ як у жінок, так і в переважної більшості чоловіків [30]. У дослідженні відзначалася задовільна пере-носимість САВ, побічні ефекти терапії були зареєстровані у 4,5% досліджуваних.…”
unclassified
“…29 Studies in which discontinuation of treatment was attempted showed a great spectrum of results, as normoprolactinaemia was maintained from as low as 0 to 6% to as high as 50 to 60% of cases over a period of 12 to 60 months after withdrawal. [34][35][36][37][38] Drawing conclusions from these studies is difficult because not all were prospective and most of them included micro-and macroadenomas and patients who had undergone neurosurgery or had received radiotherapy. However, certain of these studies observed that post-withdrawal hyperprolactinaemia was lower than that at the onset of treatment and that extending the period of treatment with dopamine agonists resulted in longer phases of remission.…”
mentioning
confidence: 99%